TRANSFORMASI HADIS-HADIS ZAKAT DALAM MEWUJUDKAN KETANGGUHAN EKONOMI PADA ERA MODERN (ZISWAF: Jurnal Zakat dan Wakaf, 2014)
Al-Qur’an and Sunnah, there are various concepts of economic development,such as zakat, infaq, and shodaqoh (giving), tijarah (trade), Qiradh(cooperatives), as well as khoraj (taxes). Everything indicates that the teaching offer values the economy and the general welfare in building community life. Zakat is one of worship Maliyah which received great attention dalam Islam. According to Islamic teachings, the universe and all its contents are the property of Allah, including the proprietary man himself.